Використання зарубіжного досвіду правового регулювання застосування спеціальних засобів поліцейськими під час професійного навчання - Боровик, М. О.; Borovyk, M. O.; ORCID: http://orcid.org/0000-0003-0943-6735; Коваленко, Б. О.; Kovalenko, B. O. (Наукові інновації та передові технології. - 2022. - №1(3). - С. 226-232, 2022)
Досліджено проблему застосування поліцейськими зарубіжних країн спеціальних засобів під час виконання службових обов’язків. Проведено загальну характеристику міжнародних нормативно-правових актів, що визначають правомірність застосування спеціальних засобів, розглянуто засоби їх реалізації. Визначено термін " спеціальні засоби несмертельної дії". Надано модель застосування силового втручання поліцейськими США, під час виконання службових обов’язків. При вивченні правових підстав застосування поліцейськими спеціальних засобів у Сполученому Королівстві Великої Британії та Північної Ірландії, було встановлено, що еквівалент їх застосування вимірюється на основі власних специфічних особливостей. Розглянуто правові обмеження діяльності чиновників поліції, щодо застосування примусових заходів в Естонській Республіці.

The scientific work is a theoretical and experimental research of the issue of the use of special means by police officers in foreign countries in the performance of official duties. The general characteristic of the international legal acts defining legality of the use of special means is carried out, the means of their implementation were considered. Based on the theoretical analysis of the researched issue the concept of "reasonable limits" was defined. This is the use of special means, in international law, which is interpreted in Anglo-American law as an additional source of law in court cases, and establishes that actions are reasonable if they are committed by a person with appropriate life and practical experience, developed level of intelligence, special knowledge to perform its powers, taking into account the conditions of a particular event, with observance of the rights of another subject of legal relations. It is pointed out about the peculiarities of the U.S. police, which consist in the fact that each state interprets the law in the field of the use of special means independently from each other. The use of special means is regulated by three types of standards that establish the limits of their use: federal standards, state standards and departmental standards. The term special means of non-lethal action (SMNLA) is defined as weapons, devices and equipment (ammunition), which are specially designed and mainly used for immediate decommissioning of personnel and military equipment with minimal fatal consequences, prevention of injuries and unwanted destruction of private property within the limits of influence. A model of the use of force by US police officers in the performance of their duties was demonstrated. In examining the legal basis for the use of special means by police in the United Kingdom of Great Britain and Northern Ireland, it was found that the equivalent of their using is measured on the basis of their own specific characteristics. Legal restrictions on the activities of police officials regarding the use of coercive measures in the Republic of Estonia were considered.

Исследована проблема применения полицейскими зарубежных стран специальных средств при исполнении служебных обязанностей. Проведена общая характеристика международных нормативно-правовых актов, определяющих правомерность применения специальных средств, рассмотрены средства их реализации. Определен термин "специальные средства несмертельного действия". Дана модель применения силового вмешательства полицейскими США, при исполнении служебных обязанностей. При изучении правовых оснований применения полицейскими специальных средств в Соединенном Королевстве Великобритании и Северной Ирландии было установлено, что эквивалент их применения измеряется на основе собственных специфических особенностей. Рассмотрены правовые ограничения деятельности чиновников полиции по применению принудительных мер в Эстонской Республике.
Using of foreign experience of legal regulation of the use of special means by police during professional training
Боровик, М. О. Використання зарубіжного досвіду правового регулювання застосування спеціальних засобів поліцейськими під час професійного навчання / Боровик Микола Олександрович, Коваленко Божена Олександрівна // Наукові інновації та передові технології. - 2022. - №1(3). - С. 226-232. - DOI:https://doi.org/10.52058/2786-5274 -2022-1(3)-226-233.
Keywords: Державне адміністративне управління. Адміністративна діяльність. State Administration. Administrative Activity. Государственное административное управление. Административная деятельность; Наукові публікації. Scientific publications. Научные публикации; поліція; police; полиция; зарубіжний досвід; foreign experience; зарубежный опыт; правове регулювання; legal regulation; правовое регулирование; Освіта. Педагогіка. Education. Pedagogy. Образование. Педагогика; професійне навчання; professional education; профессиональное обучение; спеціальні засоби; special means; специальные средства; застосування спеціальних засобів; application special means; применение специальных средств; спеціальні засоби несмертельної дії; special means of non-lethal action; специальные средства несмертельного действия; Національна поліція України. National police of Ukraine. Национальная полиция Украины; National police of Ukraine; Национальная полиция Украины; заходи примусу; coercive measures; меры принуждения; фахова підготовка; professional training; профессиональная подготовка